Evaluasi Efektivitas dan Efisiensi Standard Operating Procedure (SOP) dalam Penerimaan Calon Penghuni Baru di Rusunawa Wonocolo Kabupaten Sidoarjo - Rishad Daristama Baihaqi; Diana Hertati (Public Service and Governance Journal, 2025)
This study aims to evaluate the effectiveness and efficiency of Standard Operating Procedure (SOP) implementation in the new tenant admission process at Rusunawa Wonocolo, Sidoarjo Regency. This research employs a qualitative method using a literature review and observation approach, analyzing official documents, journals, and internship data. The findings reveal that SOP implementation at Rusunawa Wonocolo has not been fully effective or efficient. This is evidenced by inconsistencies between written procedures and field practices, limited adoption of digital technology, and a lack of transparency in the tenant selection process. Key challenges include budget constraints, reliance on manual methods, and insufficient staff training. This study recommends developing technology-based applications, such as the E-Rusun model implemented in Surabaya, to enhance service efficiency, transparency, and accountability. These findings are expected to serve as a foundation for improving public housing management and supporting the development of e-government-based public services in Sidoarjo Regency.